2020
DOI: 10.3390/molecules25030546
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cationic Prodrug of Ubiquinol-10 Enhances Intestinal Absorption via Efficient Formation of Nanosized Mixed-Micelles with Bile Acid Anions

Abstract: The aim of this study was to develop a prodrug of ubiquinol-10 (UqH-10), the active form of ubiquinone-10 (Uq-10), for oral delivery. Bioavailability of UqH-10 is hampered by its high susceptibility to oxidation and water-insolubility. We prepared three novel N,N-dimethylglycine ester derivatives of UqH-10, including a 1-monoester (UqH-1-DMG), 4-monoester (UqH-4-DMG), and 1,4-bis-ester (UqH-DMG), and assessed their physicochemical properties in vitro and in vivo. UqH-DMG spontaneously formed an aqueous micelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…The phototoxicity of Uq‐10 may limit its applicable dosage forms. We previously reported that N,N ‐dimethylglycine ester derivatives of UqH‐10 are stable for oxidation and can act as prodrugs of UqH‐10 in rats after oral administration 22 . In this study, we evaluated whether the ester prodrug strategy of UqH‐10 could avoid the photoinstability and phototoxicity demonstrated by Uq‐10 and UqH‐10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phototoxicity of Uq‐10 may limit its applicable dosage forms. We previously reported that N,N ‐dimethylglycine ester derivatives of UqH‐10 are stable for oxidation and can act as prodrugs of UqH‐10 in rats after oral administration 22 . In this study, we evaluated whether the ester prodrug strategy of UqH‐10 could avoid the photoinstability and phototoxicity demonstrated by Uq‐10 and UqH‐10.…”
Section: Discussionmentioning
confidence: 99%
“…Uq‐10 was kindly provided by Kaneka Corporation (Tokyo, Japan). Ubiquinol‐10 1,4‐bis‐ N,N ‐dimethylglycinate hydrochloride (UqH‐DMG), ubiquinol‐10 1‐mono‐ N,N ‐dimethylglycinate hydrochloride (UqH‐1‐DMG), and ubiquinol‐10 4‐mono‐ N,N ‐dimethylglycinate hydrochloride (UqH‐4‐DMG) were prepared and used as previously described 22 . Other chemicals were purchased from FUJIFILM Wako Pure Chemical Corporation (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, ASSO is insoluble in water, which results in the low bioavailability [19] and greatly limits its wide use. In addition, chemotherapeutic drugs often have serious side effects because they have no selective killing effect on normal cells and tumor cells [20].…”
Section: Introductionmentioning
confidence: 99%